2016
DOI: 10.1136/jmedgenet-2016-104302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of subsidies on cancer genetic testing uptake in Singapore

Abstract: Provision of subsidy leads to a considerable increase in genetic testing uptake rate. From the government's perspective, subsidising genetic testing may potentially reduce total costs on cancer management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…Moreover, inspection of the standardized residual loadings for items indicated that 6 items all relating to cognitive, behavioral or decisional control, were loaded together. Therefore, based on this and the domain structure posited in the paper by Tirado et al, 11 this supported the splitting of GCOS-24 into two discrete scales which were analyzed separately: (1) "Cognitive [EC] (items 4,6,8,9,11,[19][20][21][22], which encompassed hope and emotional regulation.…”
Section: Psychometric Assessment Of the Gcos-24mentioning
confidence: 70%
“…Moreover, inspection of the standardized residual loadings for items indicated that 6 items all relating to cognitive, behavioral or decisional control, were loaded together. Therefore, based on this and the domain structure posited in the paper by Tirado et al, 11 this supported the splitting of GCOS-24 into two discrete scales which were analyzed separately: (1) "Cognitive [EC] (items 4,6,8,9,11,[19][20][21][22], which encompassed hope and emotional regulation.…”
Section: Psychometric Assessment Of the Gcos-24mentioning
confidence: 70%
“…Barriers for genetic testing in Asia are multifactorial and beyond the scope of this paper, however cost of testing is a major concern for patients (Li et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported low rates of disclosure of BRCA1 / 2 genetic test results to family members and lower uptake of predictive testing among Asian compared with Western populations . Disclosure of genetic information to family is influenced potentially by the result itself, and by complex personal, cultural, and social factors .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported low rates of disclosure of BRCA1/2 genetic test results to family members and lower uptake of predictive testing among Asian compared with Western populations. 5,6 Disclosure of genetic information to family is influenced potentially by the result itself, and by complex personal, cultural, and social factors. 7,8 There are the 3 possible test results in genetic testing, which complicates the decision-making process: (1) positive (a pathogenic mutation is found and indicates an increased risk of cancers), (2) negative (no pathogenic mutation is detected), and (3) variant of uncertain significance (VUS, an alteration in the gene sequence with unknown consequence on the function of the gene product or risk of causing disease).…”
Section: Introductionmentioning
confidence: 99%